Combined supplementation of Lactobacillus fermentum and Pediococcus acidilactici promoted growth performance, alleviated inflammation, and modulated intestinal microbiota in weaned pigs - Shilan Wang; Bingqian Yao; Hang Gao; Jianjun Zang; Shiyu Tao; Shuai Zhang; Shimeng Huang; Beibei He; Junjun Wang (BMC Veterinary Research, 2019)
Abstract Background Probiotics are important for pigs to enhance health and intestinal development, which are potential alternative to antibiotics. Many studies have reported the functions of single bacterial strain as probiotic on the animals. In this study, we evaluated effects of combined probiotics on growth performance, inflammation and intestinal microbiota in weaned pigs. One hundred and eight pigs, weaned at 28 day old (7.12 ± 0.08 kg), were randomly divided into the 3 dietary treatments with 6 pens and 6 pigs per pen (half male and half female). The experimental period lasted for 28 days and treatments were as follows: i. Control: basal diet; ii. Antibiotic: the basal diet plus 75 mg· kg− 1 chlortetracycline; and iii. Probiotics: basal diet plus 4% compound probiotics. Results Supplementation probiotics improved average daily gain over the entire 28 days (P < 0.01) and feed efficiency in the last 14 days (P < 0.05) compared with the other two groups. Both probiotics and antibiotic supplementation decreased concentrations of serum pro-inflammatory cytokines interleukin-6 (P < 0.05) and interferon-γ (P < 0.01). Probiotics group had greater abundance of Lactobacillus in the caecal digesta and Firmicutes in the colonic digesta, while both probiotics and antibiotic supplementation inhibited Treponema_2 and Anaerovibrio in the caecal digesta. Caecal acetic and propionic acid (P < 0.05) of probiotics group were higher than the other two groups, whereas concentrations of colonic lactic acid and propionic acid (P < 0.05) of antibiotic group were lower than control and probiotics groups. Conclusions These findings suggest that combined supplementation of Lactobacillus fermentum and Pediococcus acidilactici regulate the gut health and improve the host ADG and F/G by decreasing serum pro-inflammatory factors (IL-6, IFN-γ), promoting beneficial bacteria (Lactobacillus in the caecal digesta and Firmicutes in the colonic digesta), enhancing production of short chain fatty acids, and inhibiting pathogens (Treponema_2, Anaerovibrio in the caecal digesta).